A randomized-controlled trial of early endotherapy versus wait-and-see policy for mild symptomatic pancreatic stones in chronic pancreatitis. Issue 8 (August 2019) - Saito, Tomotaka; Nakai, Yousuke; Mizuno, Suguru; Isayama, Hiroyuki; Sasahira, Naoki; Watanabe, Takeo; Matsubara, Saburo; Arizumi, Toshihiko; Togawa, Osamu; Hirano, Kenji; Tsujino, Takeshi; Ishigaki, Kazunaga; et al.
Abstract : Background: Although surgical or endoscopic treatment is effective for pain control in symptomatic calcified chronic pancreatitis, it is still unknown whether early intervention in mild symptomatic pancreatic stones would reduce the frequency of acute exacerbation and improve long-term outcomes. The aim of this randomized-controlled trial was to explore the efficacy of early endotherapy for mild symptomatic pancreatic stones in comparison with the wait-and-see policy. Materials and methods: Patients with mild symptoms because of pancreatic stones were assigned randomly to the endotherapy or the wait-and-see group. The wait-and-see group received endotherapy only when they developed refractory exacerbation or intractable pain. The primary outcome was the cumulative incidence of intolerable pain attacks and acute exacerbation. The secondary outcomes were the development of pancreatic insufficiency and the progression of pancreatic atrophy. Results: A total of 20 patients were enrolled between March 2008 and March 2011. The study was terminated prematurely because of the poor patient enrollment. Early endotherapy tended to reduce the cumulative incidence of pain attacks and exacerbation, ( P =0.17) with the composite incidence of pain attacks and exacerbation of 30% in the endotherapy group and 60% in the wait-and-see group. There were no significant differences in terms of diabetic status and the presence of steatorrhea. The thickness of the pancreas decreased significantly in the wait-and-see group (9.2–6.8 mm, P =0.041), but not in the endotherapy group (8.7–9.0 mm, P =0.60). Conclusion: In a small group of patients, early endotherapy in mild symptomatic chronic pancreatitis was associated with a trend toward a minor number of acute attacks and atrophy progression of the pancreas.